Pelatihan Akad Pembiayaan Syariah sebagai Upaya Mengurangi Ketergantungan Masyarakat terhadap Praktik Rentenir - Muhammad Abrar Kasmin Hutagalung; Ari Prabowo; Alim Murtani; Muhammad Ridwan; Siti Marisa Hafifah (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2026)
Interest-based lending practices by moneylenders remain a significant challenge for communities and micro-enterprises in Dusun 9, Sei Rotan Village, Percut Sei Tuan District, Deli Serdang Regency. Limited Islamic financial literacy has resulted in a lack of understanding of Sharia-compliant financing alternatives. This community service program aimed to enhance public understanding of Islamic financing contracts and encourage the utilization of Islamic financial institutions as alternative funding sources. The program employed socialization sessions, training workshops, interactive discussions, and evaluations through pre-tests and post-tests. Participants included micro and small business owners, community leaders, and local residents. The results indicated a substantial improvement in participants’ understanding of riba, murabahah, mudharabah, musyarakah, and qardh contracts. The average participant score increased from 58.4 before the training to 84.7 after the training. Furthermore, participants demonstrated a greater interest in utilizing Islamic financing services rather than interest-based loans. This program contributed to strengthening Islamic financial literacy and supporting community economic empowerment through the adoption of Sharia-compliant financing practices